Life history and habitat preference in the Darling hardyhead, Craterocephalus amniculus (Teleostei, Atherinidae) in the northern Murray‐Darling Basin, Australia. (8th March 2018) - Moy, Karl G.; Wilson, G. Glenn; Ellison, Tanya L.
Abstract: The Darling hardyhead, Craterocephalus amniculus (Atherinidae), is a threatened fish species inhabiting upstream reaches of a number of northern Murray‐Darling Basin catchments. Little is known of its life history. Our goal was to determine patterns of seasonal size structure, interannual and spatial variation in diet, and habitat selection in this species across multiple sites and years in the upper Macintyre River, northern New South Wales. Preserved specimens from a separate study were used to obtain information on diet and size structure. Size structures suggested a single annual spawning season in late September or early October. Diets varied significantly, both between years at the downstream site and among the three sites although the underlying cause of this was untested. Dietary diversity increased with distance downstream. At the two upstream sites, aquatic invertebrates made up most of the diet while over half the gut contents at the downstream site was unidentified detritus. Preference was shown for pool habitats with a sand or cobble substrate, increased channel depth and width and distance from the bank, and reduced flow velocity. Overhanging exotic riparian vegetation and in‐stream woody debris were non‐preferred. This species may be vulnerable to further population decline in light of its restricted habitat preferences and narrow spawning season. However, comparable data from nearby catchments will be necessary to ascertain the species' conservation status across its broader distribution.